CO2 solubility measurements in brine under reservoir conditions: A comparison of experimental and geochemical modeling methods. Issue 2 (17th February 2016) - Steel, Luc; Liu, Qi; Mackay, Eric; Maroto‐Valer, M. Mercedes
Abstract: The dissolution of CO2 in brine (solubility trapping) is one of the most secure and permanent trapping mechanisms when considering CO2 geological storage. In addition, CO2 dissolution in brine is an important mechanism of CO2 enhanced oil recovery as it improves sweep efficiency and increases oil displacement. Currently, there is a range of experimental methods that has been used to measure CO2 solubility in brine and a critical review of these methods is presented here. Several different geochemical models that can be used to calculate CO2 solubility in brine are also reviewed and the importance of selecting the correct equation of state (EoS) is addressed. Furthermore, the validity of the experimental results was ascertained through a comparison of the published experimental results with those produced through geochemical modeling. The geochemical modeling software, HydraFLASH, can be used to accurately calculate CO2 solubilities under a number of conditions provided the correct EoS is selected. For the purpose of CO2 ‐water systems, the Valderrama‐Patel‐Teja EoS is the most accurate as it is designed to be used for systems containing polar and non‐polar compounds. The published experimental results were compared with those obtained through the geochemical modeling, to ascertain the most accurate means of measuring CO2 solubility. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd